Metamorphic evolution and U-Pb zircon SHRIMP geochronology of the Belizario ultramafic amphibolite, Encantadas Complex, southernmost Brazil. - Hartmann, L.; Santos, J.; Leite, J.; Porcher, C.; McNaughton, Neal (Academia Brasileira de Ciencias, 2003)
The integrated investigation of metamorphism and zircon U-Pb SHRIMP geochronology of the Belizario ultramafic amphibolite from southernmost Brazil leads to a better understanding of the processes involved in the generation of the Encantadas Complex. Magmatic evidence of the magnesian basalt or pyroxenite protolith is only preserved in cores of zircon crystals, which are dated at 2257 ± 12 Ma. Amphibolite facies metamorphism M1 formed voluminous hornblende in the investigated rock possibly at 1989 ± 21 Ma. This ultramafic rock was re-metamorphosed at 702 ± 21 Ma during a greenschist facies event M2; the assemblage actinolite + oligoclase + microcline + epidote + titanite + monazite formed by alteration of hornblende. The metamorphic events are probably related to the Encantadas Orogeny (2257 ± 12 Ma) and Camboriu Orogeny (~ 1989 Ma) of the Trans-Amazonian Cycle, followed by an orogenic event (702 ± 21 Ma) of the Brasiliano Cycle. The intervening cratonic period (2000-700 Ma) corresponds to the existence of the Supercontinent Atlantica, known regionally as the Rio de la Plata Craton.